DAYA ANTIBAKTERI SEDIAAN GEL EKSTRAK ETANOL DAUN MURBEI (Morus alba L.) SEBAGAI OBAT LUKA PADA KULIT TERHADAP Staphylococcus aureus - Asri, Muhammad; Bahar, Fahril (Jurnal Riset Kefarmasian Indonesia, 2019)
A research concerning the antibacterial effect of mulberry leaves (Morusalba L.) ethanol extract gel as cure of skin wounds against Staphylococcus aureus bacteria.This research is aimed to know the antibacterial effect of mulberry leaves (Morusalba L.) ethanol extract gel as cure of skin wounds against Staphylococcus aureus bacteria and determine inhibitor concentration minimum value. It was an experimental research which conducted in the laboratory to test the antibacterial effect of mulberry leaves (Morusalba L.) ethanol extract gel as cure of skin wounds against Staphylococcus aureus bacteria. The result of observation showed that 1% concentration produced diameter of resistance zone average as 0.83 mm, 3% concentration were 0.97 mm and 5% concentration were 1.13 mm. It can be concluded that; 1) mulberry leaves ethanol extract gel stock on 1%, 3%, and 5% concentration have a weak resistance based on Antimicrobial resistor category ;2) inhibitor concentration minimum value of 1% concentration, was the lowest concentration that still giving antibacterial effect to against of Staphylococcus aureus bacterial